Anthropological Perspectives on Criminal Behavior: Understanding Cultural Contexts - Zubaedah, Putri Amalia; Hafizi, Royyan (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2023)
Anthropological Perspectives on Criminal Behavior: Understanding Cultural Contexts delves into the intricate relationship between culture and criminal behavior, employing qualitative methods and extensive literature review. This interdisciplinary study explores how cultural contexts shape and influence criminal behavior, providing insights into diverse societal norms, values, and practices. By examining various ethnographic studies and theoretical frameworks, this research aims to elucidate the complex interplay between culture, social structures, and individual actions that contribute to criminality. Through an in-depth analysis of existing literature, this article identifies key themes and patterns in anthropological research on criminal behavior, shedding light on cultural factors that underpin deviant conduct across different societies. The findings highlight the importance of understanding cultural contexts in addressing crime and developing effective interventions that are sensitive to diverse cultural perspectives. Ultimately, this study contributes to the advancement of anthropological knowledge on criminal behavior and informs future research and policy initiatives aimed at promoting social justice and reducing crime rates.